OPPORTUNITIES FOR SPEECH RESTORATION IN PATIENTS WITH MAXILLECTOMY. LITERATURE REVIEW - Ivan Gerdzhikov (Peytchinski Publishing, 2023)
Background: Over the last few years, there has been an increase in oncologic morbidity in the maxillofacial region. A significant increase in cases of cancer of the maxilla has been established. As a result of the surgical treatment of maxillary tumours, the barrier between the oral and nasal cavity is broken, which leads to serious speech disorders. Aim: The purpose of the literature review is to analyse data from different studies on the changes in speech after maxillectomy and the opportunities for its restoration with different types of dentures. Discussion: The opportunities for treatment of patients with maxillary defects include surgical restoration or obturator, as there are contradictory data on what are the optimal means of restoring speech. The predominant opinion is that the choice of treatment method depends on the size and the location of the defects, with most authors considering obturators the optimal means of treatment. Their role in the normalisation of speech function by restoring the barrier between the oral and nasal cavity is indisputably proven. Immediate prosthetics have been found to provide faster and easier recovery of speech. To preserve the achieved results, a three-stage method of treatment with surgical, temporary and definitive obturator is recommended, which restores not only speech but also normal articulation. Conclusion: Surgical treatment of cancer of the upper jaw causes defects differing in size, which seriously disturbs speech function. Depending on the size and location of the defect, specific prosthetic treatment methods are used, with different types of dentures being produced.